2020
DOI: 10.1177/2210491720950327
|View full text |Cite
|
Sign up to set email alerts
|

The “invisible” wiring technique for displaced fracture patella

Abstract: Background: Operative treatment of displaced patella fracture dates back to Lister in 1877. Nowadays, steel wires remain the material of choice in tension band technique despite complications such as wire breakage, suboptimal placement, or skin impingement. We propose using a high-tensile strength braided tape-shaped polyblend suture (FiberTape®, Arthrex, Naples, Florida, USA) as an alternative that could minimize complications related to steel wires. Method: Between February 2014 and April 2018, 15 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“… 11 Fracture fixation with suture tension bands have demonstrated high rates of fracture union and excellent outcomes. 18 , 19 , 20 Advantages of suture over metal wire include less hardware irritation with lower rates of revision surgery. 6 , 7 , 12 Furthermore, biomechanical studies have demonstrated that FiberWire (Arthrex) has greater failure strength and is superior to stainless steel in maintaining a tension band under force.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 11 Fracture fixation with suture tension bands have demonstrated high rates of fracture union and excellent outcomes. 18 , 19 , 20 Advantages of suture over metal wire include less hardware irritation with lower rates of revision surgery. 6 , 7 , 12 Furthermore, biomechanical studies have demonstrated that FiberWire (Arthrex) has greater failure strength and is superior to stainless steel in maintaining a tension band under force.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Lastly, suture is easier to handle and tighten than metal wire, which can translate to a tighter construct and decreased tourniquet and operating time. 11 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tension band technique through cannulated screws has continued to evolve, with the historic metal wires having been replaced by high strength non-absorbable sutures. Studies have demonstrated that facture fixation with suture tension bands result in excellent patient outcomes and high rates of fracture union [22][23][24]. In addition, suture tension bands cause less hardware irrigation and resultant revision surgery than metal wires [2,3,15].…”
Section: Tension Band Fixationmentioning
confidence: 99%